Spectroscopy Study of the (_28^60)Ni and Structure of the Lowest Exited (2^+,4^+ ) States by Decay (β^-) of the Cobalt Radioactive Isotope (_27^60)Co (Latakia University Journal -Basic Sciences Series, 2021)
The decay  of  isotope has been studied using a detector calibration , with an overall energy resolution . Angular distributions have been obtained for the tow transitions    and  states of . Comparison between the structures of low-lying states  and  , the ratio  , the transition , and deformation parameter   of this nuclei with the even-even nickel isotopes , , , , ,   is made and with some authors nucleus in the region where the neutrons number  and  considered magic numbers. The data have been analyzed with the Shell Model.